Adipose Tissue–Derived Regenerative Cell–Enhanced Lipofilling for Treatment of Cryptoglandular Fistulae-in-Ano: The ALFA Technique. (December 2015) - Borowski, David W.; Gill, Talvinder S.; Agarwal, Anil K.; Tabaqchali, Mohamed A.; Garg, Dharmendra K.; Bhaskar, Pud
Background . The treatment of complex fistulae-in-ano is challenging and often includes a number of operations due to high rates of recurrence. Recently, techniques using in vitro expanded adipose tissue–derived stem cells have been described. We describe a novel treatment for cryptoglandular fistulae used in 7 patients, using a combination of surgical closure of the internal opening and real-time autologous adipose tissue–derived regenerative cells (ADRC)–enhanced lipofilling, without need for in vitro expansion. Methods . Following exclusion of active perianal sepsis, patients underwent a standard tumescent liposuction procedure, harvesting ~300 to 400 mL of raw lipoaspirate. The lipoaspirate was prepared in real time, using the Celution 800/CRS system to obtain the stromal vascular fraction containing ADRCs. After excision of the fistula tract and closure of the internal orifice, fresh ADRC-enhanced lipoaspirate was injected into and around the fistula tract. Results . At 6-months' follow-up, 5 of 7 (71.4%) patients showed clinical signs of fistula closure; one of these patients had a recurrence at 10 months due to sepsis. The remaining 4 patients (57.1%) all had complete fistula closure at a median of 46 months' follow-up. There were no adverse events associated with the technique, and no new incontinence. Conclusion . Treatment of cryptoglandular fistulae-in-ano with ADRC-enhanced lipofilling appears feasible and safe, and may add to the range of procedures that can be used to treat this difficult problem.